Research on Financial Poverty Alleviation Aid for Increasing the Incomes of Low-Income Chinese Farmers - Pan, Huibo; Yao, Lili; Zhang, Chenhe; Zhang, Yuchi; Gao, Yuying (Sustainability, 2024)
Unlike the definition of absolute poverty in international society, rural poverty in China is characterized by farmers’ low ability to increase their income, and the unsustainability of income increases. This study examines farming households’ issues with increasing their incomes via financial aid from the International Fund for Agricultural Development (IFAD). Through quantile regression and stepwise regression models, this paper studies two ways in which IFAD loan projects can affect farmers’ income: by directly promoting increases in farmers’ income and by indirectly promoting increases in farmers’ income through newly operational agricultural entities. This paper uses the entropy weight and comprehensive evaluation methods to construct an IFAD evaluation index system to evaluate the endogenous development ability of farmers participating in IFAD loan projects. Our empirical results show that IFAD projects significantly and positively affect farmers’ income. Our heterogeneity analysis shows that IFAD projects have varied effects on farmers’ income growth at different income levels; the lower the income level, the more pronounced the promotion. IFAD loan projects promote farmers’ incomes through newly operational agricultural entities, the mechanism of which is their ESG performances. On average, the anti-poverty masses and areas participating in IFAD loan projects show a robust endogenous development impetus.